G239(P) A review of children presenting with a new diagnosis of diabetes. (12th March 2018) - Cockburn, CS; Rayen, B
Abstract : Introduction: Diabetic ketoacidosis (DKA) can be a life threatening presentation of Type 1 diabetes in children and young people. Data had previously been collected (from January 2007 – August 2009) that demonstrated that 30% of newly diagnosed diabetics presented in DKA. Following these results and using the Parma study, a public health awareness campaign was completed using (P)s designed by local school children to try and improve public awareness around presentations of diabetes. Aims: To review whether children presented in DKA as their first diagnosis of Type 1 diabetes and whether they had presented to health services on more than one occasion prior to diagnosis. Methods: A list of patients was collected from the Diabetic Team caseload and SCI diabetes database to identify children and young people diagnosed between January 2014 and July 2017. Case notes were retrospectively reviewed using a pro-forma that was developed in consultation with the diabetes team. 33 patients were included. Results: The majority of patients continued to be diagnosed by GP (58%), while out of hours (OOH) made 18% of diagnoses, 12% were made by the emergency department (ED) and 12% by paediatrics. Previously 55% of diagnoses were made by the GP, 10% by ED and 20% by paediatrics. Six of the thirty three patients presented in DKA (19%) with the remaining 81% (27/33) presenting 'walking wounded'. In comparison to the previous data collection which had demonstrated 30% (6 of 20) presented with DKA. 42% of patients were diagnosed at their first presentation, with a further 21% on their second presentation, 9% presented on three or more occasions before they were diagnosed. Conclusion: There has been a reduction in percentage of new diabetic children presenting in DKA to services. This may suggest a greater awareness in the community and could be related to a previous public health campaign. It is still concerning that almost 20% (1 in 5) new diabetics present with DKA and that only 42% of patients were diagnosed at initial presentation. On some occasions diabetes was suspected but the patients were asked to return with a urine sample before referral to paediatric services was made.